Pelaksanaan Pembelajaran Seni Budaya (Musik) di Kelas VIII.2 SMPN 3 Sungai Geringging - Fajar Friatma; Syeilendra Syeilendra (Dinasti Research, 2023)
The purpose of this study was to describe the implementation of learning arts and culture (music) in class VIII.2 at SMP Negeri 3 Sungai Geringging. Researchers used qualitative research that is descriptive. The main instrument in this study was the researcher himself observing the learning process for class VIII.2 on the subject matter of music at SMP Negeri 3 Sungai Geringging. The type of data used is primary and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews, and documentation. The steps to analyze the data are data collection, data reduction, data presentation, and drawing conclusions. The results of the study concluded that the process of implementing art and culture learning for music material in class VIII.2 had not gone well. This is because there are obstacles in which there are no learning media, and there is no infrastructure for musical instruments, as well as practice rooms so the teacher does not teach in accordance with the existing syllabus and lesson plan (RPP). Learning the art of music in class VIII.2 is one of them only fulfilling the core competency indicators in the syllabus, namely